(untitled) (Texas Journal of Medical Science, 2024)
The health of young people is a priority area of public health activities, because the well-being of the state depends on it. The lifestyle of medical university students is one of the basic values, since its future professional status involves training and forming the commitment of adults and children to a healthy lifestyle.